[Laiškai] / Berezovskis (Berezowski) I. - Adomui Zavadskiui. - (:unkn) unknown (My University, 1853)
2 laiškai apie sveikatos būklę, knygų atsiuntimą iš knygyno.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Zawadzki, Adam, 1814-1875